The Association between Resistance of Sepsis-Inducing Bacteria to First-Line Antibiotics and Sepsis Outcome: A Retrospective Cross-Sectional Study - Herleeyana Meriyani; Dwi Arymbhi Sanjaya; Rr. Asih Juanita; Nyoman Budiartha Siada; I Wayan Maysa Yudiartha; Kadek Suryawan (Jurnal Ilmiah Medicamento, 2026)
Background: Sepsis is a significant infectious disease linked to high mortality rates. Several bacterial pathogens that cause sepsis have shown resistance to first-line antibiotics. This resistance in sepsis-causing bacteria to initial antibiotic agents threatens treatment success, elevating mortality risk, healthcare costs, and prolonged hospital stays.Objective: This study aimed to investigate the relationship between the resistance of sepsis-causing bacteria to first-line antibiotics and sepsis treatment outcomes.Methods: This cross-sectional study was a single-center retrospective study. Data were collected from sepsis patients admitted to the intensive care unit of a general hospital in Bali between 2022 and 2023. The patients included in this study were those with a positive bacterial infection, as provided in the culture result. Therapy outcomes were evaluated based on discharge status: improved or unimproved (deceased). The resistance of sepsis-causing bacteria to first-line antibiotics, including fluoroquinolones, third- and fourth-generation cephalosporins, piperacillin-tazobactam, and vancomycin, was assessed through blood cultures. The relationship between antibiotic resistance and therapy outcomes was analyzed using the Gamma correlation coefficient. This study included 57 of 108 sepsis patients, primarily male (57.89%) and older than 60 years (57.89%).Results: A strong, significant positive correlation was observed between the resistance of sepsis-causing bacteria to third-generation cephalosporins and therapy outcomes (p=0.001; r=0.637). In contrast, resistance to fluoroquinolones (p=0.108; r=0.387), fourth-generation cephalosporins (p=0.377; r=-0.199), piperacillin-tazobactam (p=0.816; r=-0.060), and vancomycin (p=0.911; r=0.030) did not significantly impact therapy outcomes. The outcome of sepsis therapy is associated with resistance of sepsis-causing bacteria to third-generation cephalosporins but not to fluoroquinolones, fourth-generation cephalosporins, piperacillin-tazobactam, or vancomycin. This study uses a relatively small sample size, which precludes subgroup analyses.Conclusion: Non-significant findings for some antibiotics may reflect insufficient power; further study is needed to assess the correlation between resistance of sepsis-causing bacteria to fluoroquinolones, fourth-generation cephalosporins, piperacillin-tazobactam, and vancomycin.